Sensores eletroquímicos baseados em biocarvão e derivados de grafeno para a determinação de carbaril, carbendazim e paraquate em amostras de água e alimentos - Sant'Anna, Mércia Vieira da Silva (2022)
Electrochemical sensors are devices able of recognizing and quantifying species of organic or inorganic nature, with the maximum possible specificity. In this way, these devices can be applied for the detection of pesticides in diverse complex samples. According to the above, the objective of this work was to develop modified electrodes based on biochar and graphene derivatives to obtain sensors and apply for voltammetric determination of the pesticides paraquat (PQ), carbendazim (CBZ), and carbaryl (CBR) in water and food samples. Biochar samples were obtained at 400 °C (B4), 500 °C (B5) and 600 °C (B6) from the biomass of the Eichhornia crassipes species, common known as water hyacinth. The biomass and biochar samples were characterized by different analysis techniques, and it was observed that the variation of the pyrolysis temperature promoted the formation of functional groups characteristic of the degradation of lignocellulosic biomass. The acid activation of the biochar samples resulted in the formation of more oxygen and nitrogen groups on the material surface, in addition to increasing the surface area. The syntheses of graphene derivatives (graphene oxide – GO and reduced graphene oxide – rGO) resulted in the formation of characteristic nanostructures, according to the morphology and structural composition of these materials. For the determination of PQ, an electrode modified with activated biochar (B4A) and rGO (E-rGO/B4A) was developed, and it was successfully applied to samples of coconut water, wastewater, lettuce, honey, and lemon juice, showing recovery values from 87.7% to 103.8%. The electrode modified with precursor biochar and rGO (E-rGO/B4) was applied sensitively and selectively for the CBZ determination in drinking water, wastewater, lettuce leaves, and orange juice samples. Two strategies were evaluated in the stages of pre-concentration and voltammetric measurements (insitu methodology and ex-situ methodology). The ex-situ methodology presented better analytical performance and the recovery values of the developed method ranged from 77.7% to 122.0%. A new analytical method was developed for the simultaneous determination of CBZ and CBR using the E-rGO/B4 electrode, however, it presented high detection limits (11.8 µmol L -1 ) and quantification (60.0 µmol L-1 ) for CBR, which makes it feasible to apply the electrode for determination of carbendazim in the presence of carbaryl. Thus, in this work, were developed and applied new electrochemical sensors based on water hyacinth biochar and graphene derivatives for sensitive and selective determinations of pesticides in samples of a complex nature.